IMPLEMENTATION OF DECENT WORK STANDARDS ON PLATFORM WORKERS: DIFFERENT APPROACHES - Jašarević, Senad; Božičić, Darko M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
The question of the legal status of platform workers has occupied the attention of the professional public for quite a time, but still remains without an unified answer. Thus, in judicial practice there are situations where different courts make different decisions under the same or similar factual circumstances. On the other hand, there are different views in the labour law theory regarding the aformentioned question. They start from equating platform workers with the employees. This approach is undoubtedly the most favorable for platform workers because it implies that they enjoy all the employment relationship rights. Opposite to this position is the idea of introducing a certain scope of rights that would be enjoyed by platform workers. In this connection, the question arises as to what rights would that entail and to what is their scope? The answer contains several alternatives. The first is based on establishing a special legal category for platform workers, for whom the enjoyment of a limited set of rights from the employment relationship is foreseen. Second alternative comes from the ILO. In this organization’s study on digital platforms, the ILO lists three groups of rights that can and have to be applied to platform workers, citing specific sources of ILO in this regard. Although certain instruments that ensure the protection of the social and economic position of platform workers are aimed at particular occupations, the study concludes that it is about the rights that are necessary to protect the specific position of platform workers. But still the main question remains unanswerd – how to ensure the application of all those instruments and the rights contained in them to platform workers?